Aircraft Movement Simulation on the Location, Number, and Angle of Exit Taxiways at Juanda International Airport to Increase Runway Capacity - Wulan A. , Rahayuningtyas; Ahyudanari, Ervina (Jurnal Transportasi: Sistem, Material, dan Infrastruktur, 2023)
There are several runway performance evaluation analyses with various exit taxiway angles at Juanda Airport. This analysis was carried out when Juanda Airport only had one operating terminal and five exit taxiways. Current conditions show that Juanda Airport has two operating terminals with eleven exit taxiways. Analytically, it shows that the simulation value is greater than the field performance. Geometry evaluation of the exit taxiway angles indicates a discrepancy between the angles on the ground and the theoretical angles. This discrepancy will also affect the runway performance. From the three studies, it can be assumed that the location and number of exit taxiways affect runway performance.Aircraft movement simulation on location, number, and angle of exit taxiway aimed to determine whether the existing conditions can facilitate aircraft movement at both terminals. In the initial process, the aircraft movement data were collected from 2013 to 2019 to forecast aircraft movements in 2025. From the forecasting I result, it was obtained that the number of aircraft movements during peak hours was 46 movements/hour. While from the forecasting II result, it was obtained that the number of aircraft movements during peak hours was 35 movements/hour. The forecasting results were used as maximum aircraft movement data in the simulation. In the second stage, the Runway Occupancy Time (ROT) that occurred at Juanda Airport for each type of aircraft was calculated to be compared with the theoretical ROT. The comparison results showed that the actual ROT value was more significant than the theoretical ROT. The forecasting results of aircraft movements and the ROT calculation used in carrying out the simulation showed that the runway could not facilitate the forecasting results of aircraft movement going to Terminal 2. Furthermore, it combined these simulation results with the analysis results of runway end use used in the planning process of the new exit taxiway location. The planning results obtained a distance of 1,800 m and 2,140 m, measured from each end of the runway to Terminal 2. This analysis also concluded that it will need an additional runway to facilitate aircraft movement in 2025.